Amphi-functional mesoporous silica nanoparticles for dye separation - Shinde, Pravin; Sen Gupta, Sayam; Singh, Baljeet; Polshettiwar, Vivek; Prasad, Bhagavatula L. V. (Journal of Materials Chemistry A, 2017)
Synthesis of amphi-functional mesoporous silica nanoparticles (similar to 80 nm) by stepwise chemical modifications of outer and inner pore surfaces is reported. These materials display a clear "Janus" like character and are able to selectively and completely separate hydrophobic dyes form a mixture of dyes. Our results clearly suggest a clear partition of more hydrophobic dyes into the pores from a mixture of two dyes. In addition this material displays a remarkable recycling ability for 10 cycles with up to similar to 99% dye removal from water.